Squatters, Floodplain Occupation And Effects On Rivers:Some Experience From Malaysia. - Yusof, Radiah; Ismail, Nor Aini; Chan, Ngai Weng; Ibrahim, Ab. Latif (2004)
Malaysia is a rapidly developing country, one of the 'tiger' economies of Asia and on the verge of becoming a developed nation